Implants for surgery - wear of total knee-joint prostheses - part 2: methods of measurement (ISO 14243-2:2009, IDT) - Abdul Razak, Noor Hayati; Yaakop, Salbiah; Choon, David; Goonting, Tracy E.; T, Mahadevan; Law, Ching Yee; How, Kim Chuan; Singh, Harwant; Ismail, Zulkharnain; Manickam, Thirumal; Yaakob, Mohd Amin; Mohd Yusof, Hyzan; et al. (SIRIM, 2011)
ISO 14243-2:2009 specifies a method of assessment of wear of the tibial component of total knee-joint prostheses using the gravimetric technique for components tested in accordance with ISO 14243-1.